2′-O-Galloylhyperin Isolated From Pyrola incarnata Fisch. Attenuates LPS-Induced Inflammatory Response by Activation of SIRT1/Nrf2 and Inhibition of the NF-κB Pathways in Vitro and Vivo - Wang, Peng; Gao, Chang; Guo, Na; Zhang, Sun-Dong; Wang, Wei; Yao, Li-Ping; Zhang, Jing; Efferth, Thomas; Fu, Yu-Jie (Frontiers in Pharmacology, 2018)
2′-O-galloylhyperin, a major compound of Pyrola incarnata Fisch., possesses a variety of biological and pharmacological activities, including anti-oxidative and anti-inflammatory activities. Nevertheless, the underlying molecular mechanisms of 2′-O-GH in microbial infection and sepsis are not clear. In this study, we investigated the anti-inflammatory effects of 2′-O-GH. We found that 2′-O-GH significantly reduced the production of TNF-α, IL-6, and nitric oxide (NO), suppressed the expression levels of iNOS, blocked the translocation of NF-κB from the cytosol to nucleus, and decreased the MAPK activation in LPS-activated RAW 264.7 cells. 2′-O-GH also enhanced the nuclear translocation of Nrf2 and up-regulated the expression of heme oxygenase-1 (HO-1) and SIRT1. In addition, the administration of 2′-O-GH attenuated the TNF-α and IL-6 production in the serum, infiltration of inflammatory cells, liver tissue damage, and the mortality rate of LPS-challenged mice. Moreover, 2′-O-GH significantly upregulated Nrf2 and SIRT1 expression and inhibited the inflammatory responses in the liver of septic mice. The collective data indicate that 2′-O-GH could potentially be a novel functional food candidate in the treatment of sepsis.